To show:that B is the inverse of A
Explanation of Solution
Given information:
Concept Involved:
Definition of Matrix Multiplication:
If
The definition of matrix multiplication uses a row-by-column multiplication, where the entry in the
So, for the product of two matrices to be defined, the number of columns of the first matrix must equal the number of rows of the second matrix. That is, the middletwo indices must be the same.
The outside two indices give the dimension of the product as show below
Definition of the Inverse of a Square Matrix:
Let A be
If there exists a matrix
The symbol
To show that B is the inverse of A, we need to show that AB = I = BA.
Calculation:
Finding the product AB
Multiply the elements of each row of the first matrix by the elements of each column in the second matrix and add the products
Simplifying each element of the matrix further
Multiplying the ¼ with each element inside the matrix
Finding the product BA
Multiply the elements of each row of the first matrix by the elements of each column in the second matrix and add the products
Simplifying each element of the matrix further
Multiplying the ¼ with each element inside the matrix
Conclusion:
Since AB is equal to BA, A is an inverse of B.
Chapter 8 Solutions
EBK PRECALCULUS W/LIMITS
- Use the method of disks to find the volume of the solid that is obtained when the region under the curve y = over the interval [4,17] is rotated about the x-axis.arrow_forward1. Find the area of the region enclosed between the curves y = x and y = x. Sketch the region.arrow_forwardfor the given rectangular coordinates, find two sets of polar coordinates for which 0≤θ<2π, one with r>0 and the other with r<0. (-2sqrt(3),9)arrow_forward
- I circled the correct answer, could you show me how to do it using divergence and polar coordinatesarrow_forwardThe correct answer is D Could you explain and show the steps pleasearrow_forwardTaylor Series Approximation Example- H.W More terms used implies better approximation f(x) 4 f(x) Zero order f(x + 1) = f(x;) First order f(x; + 1) = f(x;) + f'(x;)h 1.0 Second order 0.5 True f(x + 1) = f(x) + f'(x)h + ƒ"(x;) h2 2! f(x+1) 0 x; = 0 x+1 = 1 x h f(x)=0.1x4-0.15x³- 0.5x2 -0.25x + 1.2 51 Taylor Series Approximation H.w: Smaller step size implies smaller error Errors f(x) + f(x,) Zero order f(x,+ 1) = f(x) First order 1.0 0.5 Reduced step size Second order True f(x + 1) = f(x) + f'(x)h f(x; + 1) = f(x) + f'(x)h + "(xi) h2 f(x,+1) O x₁ = 0 x+1=1 Using Taylor Series Expansion estimate f(1.35) with x0 =0.75 with 5 iterations (or & s= 5%) for f(x)=0.1x 0.15x³-0.5x²- 0.25x + 1.2 52arrow_forward
- EXAMPLE 3 Find S X √√2-2x2 dx. SOLUTION Let u = 2 - 2x². Then du = Χ dx = 2- 2x² = 信 du dx, so x dx = du and u-1/2 du (2√u) + C + C (in terms of x).arrow_forwardLet g(z) = z-i z+i' (a) Evaluate g(i) and g(1). (b) Evaluate the limits lim g(z), and lim g(z). 2-12 (c) Find the image of the real axis under g. (d) Find the image of the upper half plane {z: Iz > 0} under the function g.arrow_forwardk (i) Evaluate k=7 k=0 [Hint: geometric series + De Moivre] (ii) Find an upper bound for the expression 1 +2x+2 where z lies on the circle || z|| = R with R > 10. [Hint: Use Cauchy-Schwarz]arrow_forward
- Calculus: Early TranscendentalsCalculusISBN:9781285741550Author:James StewartPublisher:Cengage LearningThomas' Calculus (14th Edition)CalculusISBN:9780134438986Author:Joel R. Hass, Christopher E. Heil, Maurice D. WeirPublisher:PEARSONCalculus: Early Transcendentals (3rd Edition)CalculusISBN:9780134763644Author:William L. Briggs, Lyle Cochran, Bernard Gillett, Eric SchulzPublisher:PEARSON
- Calculus: Early TranscendentalsCalculusISBN:9781319050740Author:Jon Rogawski, Colin Adams, Robert FranzosaPublisher:W. H. FreemanCalculus: Early Transcendental FunctionsCalculusISBN:9781337552516Author:Ron Larson, Bruce H. EdwardsPublisher:Cengage Learning